A study on the factors of stress at workplace in Jabatan Imegresen Negeri Melaka - Nawawi, Mohd Ezly; Dardi, Nawal Adibah (2006)
The scope of study is focusing on the Jabatan Imegresen Negeri Melaka. This research will focus on the factors of stress at workplace to staff whereby these staffs deal with a variety of people. Besides that by focusing on this staff it will eliminate any complaint arise about their services as well as for their services improvement. Furthermore, Jabatan Imegresen Negeri Melaka is one of the government agencies which play important role in Malaysia. Their services not only locally but it relate with the international agencies due to the services function. So the environment of this Jabatan Imegresen Negeri Melaka will determine the successful in delivering the services in term of quality and quantity. Therefore, strategic planning must be taken to maintain their performance and investigation must be done in order to know future consequences of the work environment.